Outcomes and measurement instruments used in congenital melanocytic naevi research: A systematic review. Issue 4 (April 2020) - Fledderus, A.C.; Franke, C.J.J.; Eggen, C.A.M.; van Etten-Jamaludin, F.S.; van der Horst, C.M.A.M.; Brinkmann, S.J.H.; Spuls, P.I.
Summary: Background: Congenital melanocytic naevi (CMN) can have a great impact on patients' lives due to the remarkable appearance and the risk of developing melanoma and neurocutaneous melanosis. Comparison of treatment efficacy is currently hindered by the lack of standard and uniform outcome reporting; this impedes guidance on optimal management policy. To address this, we aim to perform the first step in developing a core outcome set. With this systematic review, we identified a list of domains, outcomes (including patient reported outcomes) and outcome measurement instruments used in CMN research. Methods: The review was registered in PROSPERO, registration number CRD42018095235. A search was conducted in EMBASE (Ovid), PubMed and the Cochrane Library from 2006 to January 2019. Studies with 10 or more patients, with all sizes of CMN and reporting outcomes on interventional and conservative management were included. Results: A total of 1, 285 individual studies was found; 63 studies were included. We extracted 57 different outcomes and 34 outcome measurement instruments showing large heterogeneity. Patient-reported outcomes were included in 38% of studies. Few outcome measurement instruments were described. Moreover, none of the studies reported that the used instruments were ever validated in a CMN population. Conclusion: Heterogeneity exists in outcomes and instruments used in CMN research. The development of a core outcome set may reduce this heterogeneity in future research, thereby enabling treatment comparison and eventually facilitating guidance on management. Furthermore, this overview demonstrates a need for the use and validation of (patient reported) outcome measurement instruments for CMN.